Water Soil Erosion Has Significant Impact on Creating Geomorphic Hazards in Sarkapkan District. (Raparin Journal of Humanities (RJH), 2025)
Gavrilovic’s EPM model in integration with GIS and its mathematical models combined with other indexes including natural plants, rainfall averages, temperature averages, soil samples and slope are used to determine the water induced soil erosion mass. Landsat9 satellite images especially bands four, five and ten are also utilized after classifying into 6 levels, we conclude that water soil erosion is moderate in the study area which covers the largest area of the study area with an area of 85.57 km2 and %28.69 of the total area of the study are; this is due to the density of natural plants and characteristics of the study area soil. The estimated erosion rate is between 4.59 and 6.43 m3/km2/ year. Sever erosion is only estimated at around 112 and 182 m3/km2/year with a toral area of 7.5 km2 which makes up %2.535 of the total area of the study area. Very weak erosion occupy a total area of 44.28km2 and %22.14 of the total study area. The estimated erosion mass for this category is 4.30 and 34.6 m3/km2/ year.